2016
DOI: 10.1089/ten.tea.2015.0546
|View full text |Cite
|
Sign up to set email alerts
|

Chondroinduction from Naturally Derived Cartilage Matrix: A Comparison Between Devitalized and Decellularized Cartilage Encapsulated in Hydrogel Pastes

Abstract: Hydrogel precursors are liquid solutions that are prone to leaking after surgical placement. This problem was overcome by incorporating either decellularized cartilage (DCC) or devitalized cartilage (DVC) microparticles into traditional photocrosslinkable hydrogel precursors in an effort to achieve a paste-like hydrogel precursor. DCC and DVC were selected specifically for their potential to induce chondrogenesis of stem cells, given that materials that are chondroinductive on their own without growth factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 44 publications
2
52
0
Order By: Relevance
“…While press‐fit scaffolds may be appropriate for regularly shaped cartilage defects, it may not be suitable for irregularly shaped defects. Our research group has introduced paste‐like cartilage matrix–based materials that are intended to fill irregularly shaped cartilage defects, where the paste can be crosslinked after placement to stay in place . Investigating and expanding the different forms of cartilage matrix–based products are needed to encompass various patient‐specific applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While press‐fit scaffolds may be appropriate for regularly shaped cartilage defects, it may not be suitable for irregularly shaped defects. Our research group has introduced paste‐like cartilage matrix–based materials that are intended to fill irregularly shaped cartilage defects, where the paste can be crosslinked after placement to stay in place . Investigating and expanding the different forms of cartilage matrix–based products are needed to encompass various patient‐specific applications.…”
Section: Discussionmentioning
confidence: 99%
“…Decellularized cell‐derived matrices and devitalized cell‐derived matrices are derived from secreted ECM materials from cells in vitro that are subject to decellularization procedures or only physical methods, respectively. The feasibility of using cartilage matrix was determined in several initial studies that demonstrated its potential chondroinductivity . During the initial studies, similar challenges arose and resulted in parallel developmental themes in the fabrication of cartilage ECM scaffolds using both DCC and DVC.…”
Section: Introductionmentioning
confidence: 99%
“…Tissues that undergo only physical decellularization, specifically freeze‐thawing, are considered to be devitalized but not decellularized, as the cells have been lysed, but the cell debris and genetic material still remain within the processed tissue. These samples are most often processed into particles, during which the tissues go through a combination of freeze‐thawing and lyophilization, and are then ground into powder using a freezer/mill . Devitalized tissue particles have been shown to have higher quantities of ECM components, such as GAGs, than those that have been additionally treated with chemical/enzymatic decellularization methods .…”
Section: General Methods Of Decellularizationmentioning
confidence: 99%
“…Cells (chondrocytes or mesenchymal stem cells) are encapsulated in MeHA hydrogels functionalized with methacrylated chondroitin sulfate, devitalized cartilage microparticles or N-cadherin mimetic peptides (Figure 4C). These encapsulated cells demonstrate increased expression of cartilage markers and deposition of collagen type II compared with those encapsulated in pristine MeHA hydrogels [98,112,113]. In addition, MeHA/GelMA hybrid hydrogel has been used to engineer 3D in vitro fibrotic heart valve tissue models for understanding the process of fibrotic remodeling and calcification in heart valve diseases [107,114,115].…”
Section: Synthesis Properties and Recent Biomedical Applications Of Phmentioning
confidence: 99%